2019
DOI: 10.1002/pssb.201800578
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Magnetic Component in Synthetic Goethite (α‐FeOOH) and its Relation with Morphological and Structural Characteristics

Abstract: Goethite (α‐FeOOH) is by definition an antiferromagnetic (AFM) material. In the present work an investigation of the magnetic properties of goethite is performed, studying the magnetic component of this material in different samples and relating these properties with its structural and morphological characteristics. Samples are synthetized in two distinct ways in order to generate solids with different degrees of structural defects and imperfections. Electron spin resonance (ESR) data show that the sample synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
(78 reference statements)
1
3
0
Order By: Relevance
“…For 2L-Fh, the particle size obtained was less than the typical size of 2-lines ferrihydrite particles (2-5 nm) [39]. For goethite, the crystallite sizes resulted from the principal crystallographic planes, which were in line with the results reported by Valezi et al [42]. With respect to the AMO, the particle size was calculated considering the three peaks that denote crystalline forms, since these particles would have been the largest in the material structure.…”
Section: Particle Sizesupporting
confidence: 85%
See 1 more Smart Citation
“…For 2L-Fh, the particle size obtained was less than the typical size of 2-lines ferrihydrite particles (2-5 nm) [39]. For goethite, the crystallite sizes resulted from the principal crystallographic planes, which were in line with the results reported by Valezi et al [42]. With respect to the AMO, the particle size was calculated considering the three peaks that denote crystalline forms, since these particles would have been the largest in the material structure.…”
Section: Particle Sizesupporting
confidence: 85%
“…Four NMOs (2L-Fh, goethite, AMO and FMBO) were synthetized and properly characterized. FTIR [4,31], XRD [39,42] and Mössbauer spectroscopy [2,53,54] confirmed that 2L-Fh and goethite were well synthesized, with adequate particle size [39,42], PZC [6,19,20,[23][24][25]39] and specific surface area [9,46]. Conversely, the AMO XRD pattern (Figure 2c) confirmed that an amorphous Mn oxide was obtained, and it was undergoing a crystallinity process, as a mixture of manganese oxides [33,40].…”
Section: Discussionmentioning
confidence: 88%
“…The wide resonance line (g ≈ 2.1) shows parameters (Table 1) similar to iron oxides, as goethite (Valezi et al, 2016(Valezi et al, , 2019 and ferrihydrite (Siqueira et al, 2011). The resonance in the center of the six field marker lines (g varying between 2.011 and 2.013), which can be found in some seed's spectra, is identified as a free radical signal.…”
Section: Resultsmentioning
confidence: 96%
“…29 Fe-based oxides, hydroxides, and complexes were not reduced to iron, whereas iron glycolate and iron alkoxide were utilized to synthesize Fe-oxides in polyols. [30][31][32] Therefore, the direct reduction of Fe in ethylene glycol was presumed to be due to lack of evidence of a reducible intermediate complex within the reaction duration of a few seconds.…”
Section: Introductionmentioning
confidence: 99%